HUBUNGAN PEMAHAMAN NILAI KEMANUSIAAN DALAM SILA KEDUA PANCASILA DENGAN SIKAP EMPATI SISWA SEKOLAH DASAR - Tasya Shalsabilla Firdhaus; Ida Sulistyawati (Jurnal Binagogik, 2024)
Pancasila emphasize the importance of human values, one of which is empathy to be understood andaccepted by Indonesian society. The importance of empathy attitude in everyday life and how a lack ofempathy attitude can result in actions that are very detrimental to others. This is in line with thisresearch, which is to find out the correlation between understanding the value of humanity in the secondprecept of pancasila and the empathy attitude of elementary school students. This research employsquantitative research methods with a population of all students in class VI of SDN Keboan Anom. Thesampling technique used is simple random sampling, with a total of 91 students. The data collectionmethods used were test and questionnaires. The data analysis technique used is descriptive analysis,normality and linearity prerequisite test, then continued with product moment correlation hypothesistesting. Based on the results shown by the statistical analysis of SPSS 26, it is found that there is nocorrelation between understanding the value of humanity in the second precept of pancasila andempathy attitude. This implies that a high understanding of the value of humanity in the second preceptof pancasila does not necessarily mean that empathy attitude is also high. Understanding the value ofhumanity in the second precept of pancasila can provide a good moral foundation for a student, but theimplementation of these values in daily life, especially empathy attitudes is also influenced by manyother factors.